THE IMPACT OF COMORBIDITIES IN STABLE ANGINA PECTORIS CLASS I PATIENTS ON MEDICATION COSTS: A CASE STUDY - Maria, Roma Ave; Anggoro, Adi; Imtiyaz, Salwa Azzah; Halim, Muchlis (Indonesian Journal of Health Science, 2026)
Stable angina pectoris class I is a cardiovascular condition requiring long-term therapy, significantly contributing to medication costs for patients and the National Health Insurance (JKN). This study, titled “The Impact of Comorbidities in Stable Angina Pectoris Class I Patients on Medication Costs: A Case Study at Hasan Sadikin Hospital, Bandung, December 2023,” aims to analyze drug cost distribution based on therapeutic regimens (preventive, first-line, and second-line treatments) among patients with and without comorbidities such as hypertension, diabetes mellitus, and hypercholesterolemia. Using a quantitative cross-sectional design with retrospective data from medical records, 300 outpatients diagnosed with stable angina pectoris class I were selected through purposive sampling according to specific criteria. Data collected included demographics, comorbidity profiles, therapeutic regimens, and drug costs. Multiple linear regression was applied to determine the effect of comorbidities on medication expenses. The findings are expected to describe medication cost distribution across therapeutic lines and reveal the impact of comorbidities on outpatient treatment costs. Results may serve as input for BPJS Kesehatan and hospitals in evaluating cost efficiency and highlight the importance of preventing comorbid conditions to reduce treatment expenses.